Always Unique, the Lucidity of the Oxymoron: Секогаш единствена, луцидноста на оксиморонот - Kulavkova, Katica; Ruskovska, Rodna (Identities: Journal for Politics, Gender and Culture, 2004)
Author(s): Katica Kulavkova | Катица Ќулавкова Title (English): Always Unique, the Lucidity of the Oxymoron Title (Macedonian): Секогаш единствена, луцидноста на оксиморонот Translated by (Macedonian to English): Rodna Ruskovska | Родна Русковска Journal Reference: Identities: Journal for Politics, Gender and Culture, Vol. 3, No. 2 (Winter 2004) Publisher: Research Center in Gender Studies - Skopje and Euro-Balkan Institute Page Range: 9-14 Page Count: 6 Citation (English): Katica Kulavkova, “Always Unique, the Lucidity of the Oxymoron,” translated from the Macedonian by Rodna Ruskovska, Identities: Journal for Politics, Gender and Culture, Vol. 3, No. 2 (Winter 2004): 9-14. Citation (Macedonian): Катица Ќулавкова, „Секогаш единствена, луцидноста на оксиморонот“, Идентитети: списание за политика, род и култура, т. 3, бр. 2 (зима 2004): 9-14.